Gambaran Kecemasan Pada Pasien Selama Perawatan Gigi Tiruan Cekat(Kajian pada pasien di RSGM-P FKG Universitas Trisakti) - Vanessa Sirait, Zevanya; Pratama Sarwono, Aditya (Jurnal Kedokteran Gigi Terpadu, 2024)
Background: Anxiety is a human emotion that causes a feeling of worry, tension, and discomfort. In dentistry, anxiety is known as dental anxiety, which is the cause of symptoms of psychological disorders, such as depression, fear, and feelings of discomfort towards dental treatment. Dental anxiety is related to age, gender, education level, history of traumatic dental experience, and knowledge of dental care. One of the dental treatments is fixed dentures. Ideally, tooth loss should be replaced to anticipate various disorders that can occur. However, many have not done denture treatment to replace missing teeth, and anxiety is one of the reasons someone did not do denture treatment. Objective: To describe the level of anxiety in patients undergoing fixed denture treatment. Method: This type of research is descriptive observational with a cross-sectional design. This research was conducted by distributing a questionnaire containing 9 questions regarding the treatment of fixed dentures. Results: The results of this study indicate patient anxiety with a low anxiety level of 23.3%, a moderate anxiety level of 70%, and a high anxiety level of 6.7%. Female patients have a higher level of anxiety than men. Patients with adulthood have a higher level of anxiety than the elderly. Patients with primary and secondary education levels have the highest anxiety levels, and patients with the 2nd and 3rd number of visits also have the highest anxiety levels. Conclusion: Most of the fixed denture patients at RSGM-P FKG Usakti have moderate anxiety levels.